The Incidence and Risk Factors of Cholelithiasis Development After Bariatric Surgery in Saudi Arabia: A Two-Center Retrospective Cohort Study - Aldriweesh, Mohammed A.; Aljahdali, Ghadeer L.; Shafaay, Edi A.; Alangari, Dalal Z.; Alhamied, Nawaf A.; Alradhi, Hadeel A.; Yaqoub, Amirah S.; El-Boghdadly, Sami; Aldibasi, Omar S.; Adlan, Abdallah A. (Frontiers in Surgery, 2020)
Background: Rapid weight loss after bariatric surgery is a known risk factor for cholelithiasis development. This study aimed to estimate the incidence of cholelithiasis following bariatric surgery among morbidly obese patients who underwent bariatric surgery. Methods: This is a retrospective cohort study of all morbidly obese patients who underwent bariatric surgery in King Abdulaziz Medical City (Riyadh, Saudi Arabia) or King Abdulaziz Hospital (Al Ahsa, Saudi Arabia) between January 2015 and December 2018. Patients with a history of cholecystectomy or previous bariatric surgery were excluded. We estimated the incidence rate of cholelithiasis among the cohort. We also examined the associated risk factors of cholelithiasis development. Results: The study cohort contained 490 patients (38.7% males; 61.43% females) with a mean age of 36.87 ± 11.44 years. Most patients (58.54%) were followed-up for 12 months. The incidence of cholelithiasis post-operation was 6.53% (n = 32). The average period of cholelithiasis formation was 12–24 months. The percentage of total weight loss (TWL%) was significantly associated with the development of cholelithiasis post-operatively. Conclusion: A significant association was found between weight loss following bariatric surgery and the incidence of cholelithiasis. Gender, age, and comorbidities were not associated with the formation of cholelithiasis. We recommend regular follow-up appointments with thorough patient education about gradual weight loss to reduce the risk of developing cholelithiasis.